Ablation of Rami Communicans in Patients with Symptomatic Schmorl's Nodes: A Case Report - Henny Widyastuti (HM Publisher, 2023)
Introduction: Schmorl's node is a herniation or extrusion of an intervertebral disc nucleus into the end plate of an adjacent vertebral body. This case study aims to report a patient with symptoms of axial pain followed by MRI overview that supports the clinical symptoms. Presentation case: A man, 36 years old, working as a soldier, came to the hospital with complaints of low back pain. The patient is referred by an orthopedic doctor. The patient complained of lower back pain 2 years ago. Initially, the pain was intermittent, but in recent months it has been continuous. The pain gets worse when the patient gets out of bed, moves, and performs movements such as bowing, breathing, and coughing. The pain subsides when the patient is in a lying position. Physical examination showed pain intensity based on a visual analogue scale (VAS) 8-9/10. Examination of the extremities showed 5/6 motor strength in all extremities. Facet loading test: positive extension, forward bending (+). Anteroposterior/lateral lumbosacral X-ray examination showed no abnormalities. MRI examination showed degenerative disc disease and Schmorl's nodes corpus VL 1-2-4-5 (Figure 1). The patient was diagnosed with chronic discogenic et causa Schmorl’s node pain. Conclusion: Ablation of rami communicans is useful in the management of Schmorl's node pain.